CdSe (quantum dots)–graphene oxide system for thiophene polymerization: a new strategy, a new material. Issue 30 (8th March 2016) - Rusen, Edina; Diacon, Aurel; Mocanu, Alexandra; Gavrilă, Raluca; Nistor, Leona Cristina; Dinescu, Adrian
Abstract : This study presents a novel method for the oxidative polymerization of thiophene (T ) by employing cadmium selenide (CdSe) quantum dots and CdSe–graphene oxide (GO ) as activators of the polymerization system. Abstract : This study presents a novel method for the oxidative polymerization of thiophene (T ) by employing cadmium selenide (CdSe) quantum dots and CdSe–graphene oxide (GO ) as activators of the polymerization system. The polymerization initiation mechanism is based on the difference between the HOMO–LUMO energy levels of the components, which permits the formation of a donor–acceptor exchange. Thus, T should act both as acceptor and donor for a component with suitable HOMO–LUMO energy levels. We have investigated the polymerization reaction evolution as well as the molecular weights of the obtained polymers. The resulting materials containingPT, CdSe quantum dots andGO have been characterized by FTIR, UV-vis, fluorescence, HRTEM, conductivity and AFM analyses.